Multifaceted involvements of Paneth cells in various diseases within intestine and systemically - Cui, Chenbin; Wang, Xinru; Li, Lindeng; Wei, Hongkui; Peng, Jian (Frontiers in Immunology, 2023)
Serving as the guardians of small intestine, Paneth cells (PCs) play an important role in intestinal homeostasis maintenance. Although PCs uniquely exist in intestine under homeostasis, the dysfunction of PCs is involved in various diseases not only in intestine but also in extraintestinal organs, suggesting the systemic importance of PCs. The mechanisms under the participation of PCs in these diseases are multiple as well. The involvements of PCs are mostly characterized by limiting intestinal bacterial translocation in necrotizing enterocolitis, liver disease, acute pancreatitis and graft-vs-host disease. Risk genes in PCs render intestine susceptible to Crohn’s disease. In intestinal infection, different pathogens induce varied responses in PCs, and toll-like receptor ligands on bacterial surface trigger the degranulation of PCs. The increased level of bile acid dramatically impairs PCs in obesity. PCs can inhibit virus entry and promote intestinal regeneration to alleviate COVID-19. On the contrary, abundant IL-17A in PCs aggravates multi-organ injury in ischemia/reperfusion. The pro-angiogenic effect of PCs aggravates the severity of portal hypertension. Therapeutic strategies targeting PCs mainly include PC protection, PC-derived inflammatory cytokine elimination, and substituting AMP treatment. In this review, we discuss the influence and importance of Paneth cells in both intestinal and extraintestinal diseases as reported so far, as well as the potential therapeutic strategies targeting PCs.